Operations research : an introduction - Taha, Hamdy A. (Upper Saddle River, N.J. : Pearson/Prentice Hall, 2007)
Operations Research: An Introduction, 9/e is ideal for or junior/senior undergraduate and first-year graduate courses in Operations Research in departments of Industrial Engineering, Business Administration, Statistics, Computer Science, and Mathematics. This text streamlines the coverage of the theory, applications, and computations of operations research. Numerical examples are effectively used to explain complex mathematical concepts. A separate chapter of fully analyzed applications aptly demonstrates the diverse use of OR. The popular commercial and tutorial software AMPL, Excel, Excel Solver, and Tora are used throughout the book to solve practical problems and to test theoretical concepts.
Chapter 1: What Is Operations Research? -- Chapter 2: Modeling with Linear Programming -- Chapter 3: The Simplex Method and Sensitivity Analysis -- Chapter 4: Duality and Post-Optimal Analysis -- Chapter 5: Transportation Model and Its Variants -- Chapter 6: Network Models -- Chapter 7: Advanced Linear Programming -- Chapter 8: Goal Programming -- Chapter 9: Integer Linear Programming -- Chapter 10: Heuristic and Constraint Programming -- Chapter 11: Traveling Salesperson Problem -- Chapter 12: Deterministic Dynamic Programming -- Chapter 13: Deterministic Inventory Models -- Chapter 14: Review of Basic Probability -- Chapter 15: Decision Analysis and Games -- Chapter 16: Probabilistic Inventory Models -- Chapter 17: Markov Chains -- Chapter 18: Queuing Systems -- Chapter 19: Simulation Modeling -- Chapter 20: Classical Optimization Theory -- Chapter 21: Nonlinear Programming Algorithms.
Includes bibliographical references and index.
1
Keywords: Operations research; Programming (Mathematics)